2014
DOI: 10.1108/qae-07-2013-0031
|View full text |Cite
|
Sign up to set email alerts
|

Rankings, accreditation, and the international quest for quality

Abstract: Purpose – This paper seeks to analyze the internationalization of quality practices in higher education. In light of insufficient theorization about quality in the global dimension, the paper presents a model for value construction in higher education. Design/methodology/approach – The authors reviewed different models for quality in higher education vis-à-vis emerging international quality practices in higher education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 45 publications
0
49
0
5
Order By: Relevance
“…Nesta abordagem, a qualidade torna-se sinônimo de "melhores" práticas e diretrizes provenientes de instituições altamente conceituadas no mercado, a serem seguidas por entrantes e sobreviventes do segmento. Sua utilização acompanha o início dos debates acerca da transparência dos sistemas de educação superior, decorrente no início dos anos 1990, período no qual a "qualidade" torna-se justificativa para a aplicação de processos de mensuração, controle e regulação, saciando a necessidade social por transparência e accountability do período (BLANCO-RAMÍREZ;BERGER, 2014;ELASSY, 2015;GREEN, 1994;HARVEY, 2006).…”
Section: Qualidade Na áRea Da Educação Superiorunclassified
See 1 more Smart Citation
“…Nesta abordagem, a qualidade torna-se sinônimo de "melhores" práticas e diretrizes provenientes de instituições altamente conceituadas no mercado, a serem seguidas por entrantes e sobreviventes do segmento. Sua utilização acompanha o início dos debates acerca da transparência dos sistemas de educação superior, decorrente no início dos anos 1990, período no qual a "qualidade" torna-se justificativa para a aplicação de processos de mensuração, controle e regulação, saciando a necessidade social por transparência e accountability do período (BLANCO-RAMÍREZ;BERGER, 2014;ELASSY, 2015;GREEN, 1994;HARVEY, 2006).…”
Section: Qualidade Na áRea Da Educação Superiorunclassified
“…De 2010 em diante, uma qualidade perfeita não é mais considerada um objetivo de possível alcance aos sistemas educacionais, o que gera questionamentos acerca de sua existência, resultando em uma desconstrução na pós-modernidade que lhe atribui caracteres sociais de cunho democrático (BERTOLIN, 2009;BLANCO-RAMÍREZ;BERGER, 2014).…”
Section: Qualidade Na áRea Da Educação Superiorunclassified
“…Para las instituciones de Educación Superior, el tema se expresa más en prácticas que en conceptualizaciones de calidad, traducidas en la convergencia internacional de políticas, la expansión de los sistemas de acreditación (particularmente de influencia estadounidense) y los rankings (Blanco-Ramírez & Berger, 2014).…”
Section: Entre Reputación Y Calidad: La Dicotomía De Las Escuelas De unclassified
“…HEI quality is part of the larger purpose of providing value to learners and other stakeholders based on responding to institutional surroundings influencing relevance, access and investment (Blanco-Ramirez & Berger, 2014). Consequently, as Asif et al, (2013) observed, when HEIs use techniques such as QFD these should draw and expand upon existing institutional knowledge.…”
Section: Challenge 3: Integration Of Qfd With Other Hei Decision Makimentioning
confidence: 99%